PENYEDIAAN SARANA DAN PRASARANA PEMERIKSAAN KESEHATAN YANG ERGONOMIS PADA KEGIATAN RAPAT KERJA PDM DI UNIVERSITAS MUHAMMADIYAH A.R FACHRUDDIN - Suryo Sulistyo; Yogi Priyo Istiyono; Soerahman Soerahman; La Ode Akbar Rasydy; Syamsudin Syamsudin; Roby Candra; Nuriyatul Fhatonah; Anni Rohimah (Jurnal Abdimas Bina Bangsa, 2024)
The inauguration activities of regional administrators and PDM Muhammadiyah work meetings are activities that are held every five years, on this occasion these activities were carried out at Muhammadiyah A.R Fachruddin University. For this reason, Muhammadiyah A.R Fachruddin University held a free inspection program at this event because it was necessary, according to the program plan the health examination does not provide adequate facilities and infrastructure, for this reason we are providing community service by converting the classroom closest to the activity into an examination room by adding chairs and tables for examinations and a medical team and medicines as well as an ergonomic hospital bed. . The aim of this research is to determine facilities and infrastructure as well as an ergonomic layout that will be used as a guide for similar activities in emergency situations and conditions. The methods used in this research are location observation and interviews as well as assessments from users of facilities and infrastructure regarding comfort, safety, health and effectiveness